A notational analysis system for kayak and rowing analysis - Howorth, B.; Lauder, M. (2001)
The simplest form of notational analysis is the recording of the sequence, position and frequency of events. An 'event' is simply any object or happening of interest. In sprint kayaking and rowing, stroke frequency and stoke length are important factors that coaches use to analyse performance. There exist simple measures of each, however there is a need, particularly at a top level, for accurate measures of these factors. Computer systems can be used to gain such information, however, time involved and the cost of software far outweighs the cost of traditional methods. It was the aim of this project to design a simple video based notational analysis software package. The rationale for the design was to provide a software package for kayaking and rowing that could be interfaced with existing composite and S-video (50Hz) technology and recent digital video (50 - 200Hz) technology to provide a portable, quick and simple analysis and feedback package. The basic package developed incorporates the interfacing of the Panasonic AG-7350 through a RS232 serial port, technology that is available to most sport science laboratories, and a video capture board via the Microsoft for Windows Application Programming Interface (API). The interface allows the full control of the VCR thus enabling a hands-free approach to identifying and recording clips. The notation package has a three-tier approach. It allows the user to identify and mark clips of interest, name events of interest and record the occurrence of these events at the speed of playback desired. The programme then allows the user to plot the frequency data or export the data for further analysis. The package allows clips to be captured and stored to the hard drive for feedback purposes and for clips to be captured for two-dimensional digitisation. The digital video package interfaces with the camera for playback purposes, thus leading to the development of a portable package that has been used by the World Class Performance Sport Science Support Project for the British Canoe Union. This paper will present the successful application of the package within this sport in providing support to athletes preparing for the Sydney 2000 Olympics.